Pengaruh Implementasi Balanced Scorecard Terhadap Kinerja Perusahaan pada PT Gramedia Asri Media - Muhammad Fajar Kamal dan Nurahma Tresani (Universitas Tarumanagara, 2019)
This study aims to determine the effect of implementation scorecard that divided into 4 perspectives, it called financial perspective, customer perspective, perspective internal business processes, and learning & growth perspective on the performance of PT. Gramedia Asri Media. PT Gramedia Asri Media is a company of retail industry. The method used in this study is a survey with an associative type of research. The analysis starts with collecting data obtained from the distribution of questionnaires with the intended analysis unit, namely the store manager of PT Gramedia Asri Media. The data obtained is processed using the SPSS 20 application with simple regression analysis techniques and multiple regression. The results of this study indicate that Financial Perspective has a significant influence on company performance, Customer Perspective has a significant influence on company performance, Perspective Internal Business Processes have a significant influence on company performance, Learning & Growth Perspective has a significant influence on company performance, and Learning & Growth Perspective has the largest coefficient of determination. It can be concluded that the implementation of the Balanced Scorecard affects the performance of the company PT Gramedia Asri Media.